Sustainable energy generation from water splitting using trimetallic layered-double hydroxide and graphitic carbon nitride nanocomposite - Syed Haider Ali Shah; Afzal Shah; Iltaf Shah (Discover Sustainability)
Abstract Herein we report for the first time a composite material that integrates layered double hydroxides (LDH) with graphitic carbon nitride (g-C3N4), specifically tailored for water splitting application. Trimetallic LDH were synthesized through a co-precipitation method. The glassy carbon electrode (GCE) modified with the synthesized composite catalyst CuNiFe/g-C3N4/GCE showed remarkable electrocatalytic performance for the hydrogen evolution reaction (HER), achieving an overpotential of 240 mV at a current density of 10 mA/cm2 in acidic conditions. Likewise, for the oxygen evolution reaction (OER), the CuNiFe/g-C3N4/GCE recorded an overpotential of 320 mV at 10 mA/cm2 in alkaline conditions. The innovative electrocatalyst developed demonstrated remarkable efficiency in water-splitting applications, as evidenced by a peak current density of 125 mA/cm2 and − 42.5 mA/cm2 with Tafel slopes of 64.4 mV/dec and 82.5 mV/dec in alkaline and acidic environments of pH levels 13 and 0.3, respectively. Chronoamperometry validated the sustained effectiveness of the electrocatalyst. Electrochemical impedance spectroscopy revealed efficient charge transport through the modified GCE. Moreover, the synthesized catalyst demonstrated recoverability with favorable onset and overpotentials.